Calculation of mode III stress intensity factors for two interacting cracks in elastic spaces - Wong, Daryl Wai Mun (2015)
Fracture mechanics studies the propagation of cracks in materials. In the framework of linear elasticity, the stresses at the crack tips are singular. The stress intensity factors which are coefficients of the singular stress at the crack tips are used as criteria for determining the stability of cracks. They depend on the geometry of the sample, size and locations of the cracks as well as the magnitude and distribution of loads on the sample.